Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 79 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Brassica L.", "Country is China", "BasisOfRecord is Living Specimen" ] } The dataset includes 79 records from 4 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0000292-150504100648427/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences